Preventing Foodborne Illness: Salmonellosis - Keith R. Schneider; Renée M. Goodrich-Schneider; Michael A. Hubbard; Sarah Z. Waithe (EDIS)
Revised! FSHN0214, a 4-page fact sheet by Keith R. Schneider, Renée Goodrich Schneider, Michael A. Hubbard, and Sarah Z. Waithe, provides the processing and retail sector with information about preventing this disease caused by bacteria that is widespread in the environment and associated with all animal species — what it is, symptoms, who is at risk, foods associated with Salmonella, as well as good practices for receiving, handling, processing, and storage. Includes references. Published by the UF Department of Food Science and Human Nutrition, September 2009.